Characterization of in vitro metabolites of irisflorentin by rat liver microsomes using high‐performance liquid chromatography coupled with tandem mass spectrometry. (3rd March 2016) - Jia, Yan‐Wei; Zeng, Zhong‐Qiu; Shi, Hai‐Li; Liang, Jian; Liu, Yi‐Ming; Tang, Ya‐Xiong; Liao, Xun
Abstract: Belamcanda chinensis has been extensively used as antibechic, expectorant and anti‐inflammatory agent in traditional medicine. Irisflorentin is one of the major active ingredients. However, little is known about the metabolism of irisflorentin so far. In this work, rat liver microsomes (RLMs) were used to investigate the metabolism of this compound for the first time. Seven metabolites were detected. Five of them were identified as 6, 7‐dihydroxy‐5, 3′, 4′, 5′‐tetramethoxy isoflavone (M1), irigenin (M2), 5, 7, 4′‐trihydroxy‐6, 3′, 5′‐trimethoxy isoflavone (M3), 6, 7, 4′‐trihydroxy‐5, 3′, 5′‐trimethoxy isoflavone (M4) and 6, 7, 5′‐trihydroxy‐5, 3′, 4′‐trimethoxy isoflavone (M5) by means of NMR and/or HPLC‐ESI‐MS. The structures of M6 and M7 were not elucidated because they produced no MS signals. The predominant metabolite M1 was noted to be a new compound. Interestingly, it was found to possess anticancer activity much higher than the parent compound. The enzymatic kinetic parameters of M1 revealed a sigmoidal profile, with V max = 12.02 μm /mg protein/min, K m = 37.24 μm, CL int = 0.32 μL/mg protein/min and h = 1.48, indicating the positive cooperation. For the first time in this work, a new metabolite of irisflorentin was found to demonstrate a much higher biological activity than its parent compound, suggesting a new avenue for the development of drugs from B. chinensis, which was also applicable for other herbal plants. Copyright © 2016 John Wiley & Sons, Ltd.